Kesabaran dalam Regulasi Emosi pada Santri di SMA Al Muqoddasah - Shafira Dzata Shabrina Wulandari; Ari Khusumadewi (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
This study aims to empirically determine the emotional regulation of students at Al Muqoddasah High School, which focuses on the aspects of emotional regulation, factors that influence emotional regulation, and the patience of students. This research is a qualitative research with a study focused on emotion regulation and uses a phenomenological research design, and uses a Gross’s theory of emotion regulation as a reference in the analysis. The subjects of this study were one male student and one female student. The data collection technique is done by interview and documentation methods. Meanwhile, data analysis was performed using data reduction techniques, data presentation, verification, and conclusion drawing. The results of this study are the differences in aspects and emotional regulation factors possessed by the two students, as well as patience in dealing with existing problems. This study provides an overview of aspects of emotion regulation that affect the way students regulate their emotions; factors that affect emotion regulation such as the relationship between parents and children, gender, and interpersonal relationships; and patience of students as a form of regulation of positive emotions of students in dealing with the problems they have The conclusion of this study is that both students have aspects of emotional regulation and factors that influence emotional regulation, although both of these indicators are not owned by both of them as a whole, and the patience possessed by both students is not completely perfect.